2009
DOI: 10.1016/j.jcmg.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Nongated Multidetector Computed Tomography for Detection of Left Atrial Thrombus in Patients Undergoing Catheter Ablation of Atrial Fibrillation

Abstract: In patients referred for CAAF, MDCT is a sensitive (100% sensitivity) imaging modality that could be used alone especially in patients age <52 years with a CHADS(2) score <1. Incorporation of these findings could decrease the need for multiple imaging modalities and thereby reduce cost of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 18 publications
2
68
0
2
Order By: Relevance
“…3,4) As the LAA represents one of the major sources of cardiac thrombus formation responsible for stroke in patients with AF, 5,6) the imaging of the different structures and lobes is of utmost importance to diagnose the presence of thrombus, especially in patients with non-valvular AF. 7,8) Multidetector computed tomography 9) and contrast-enhanced magnetic resonance imaging 10) are able to image the LAA; however, it was concluded that magnetic resonance imaging lacks diagnostic accuracy for the detection of LAA thrombi. 10) Transesophageal echocardiography (TEE) is the gold standard to detect LAA thrombus, 11) but false positive results still occur.…”
mentioning
confidence: 99%
“…3,4) As the LAA represents one of the major sources of cardiac thrombus formation responsible for stroke in patients with AF, 5,6) the imaging of the different structures and lobes is of utmost importance to diagnose the presence of thrombus, especially in patients with non-valvular AF. 7,8) Multidetector computed tomography 9) and contrast-enhanced magnetic resonance imaging 10) are able to image the LAA; however, it was concluded that magnetic resonance imaging lacks diagnostic accuracy for the detection of LAA thrombi. 10) Transesophageal echocardiography (TEE) is the gold standard to detect LAA thrombus, 11) but false positive results still occur.…”
mentioning
confidence: 99%
“…CT identified LAA filling defects with a sensitivity, specificity, positive and negative predictive values of 93%, 85%, 31% and 99% respectively, as compared to TEE (Kim et al, 2007). These results have been recently confirmed by Martinez et al in a cohort of 402 patients (Martinez et al, 2009). Overall, 362 patients (91%) had no evidence of a filling defect by CT or left atrial spontaneous echo contrast or thrombus by transesophageal echocardiography.…”
Section: Ct Imaging To Diagnose Laa Thrombosismentioning
confidence: 64%
“…Current literature includes both prospective and retrospective cross-sectional studies, and a meta-analysis [5,[7][8][9][10][11][12][13]18]. Study sizes have varied from 72 to 402 patients [7,9], yet current literature remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Study sizes have varied from 72 to 402 patients [7,9], yet current literature remains controversial. Martinez et al [9] found sensitivity and specificity of CCT to be 100% and 92%, respectively concluding that TEE is unnecessary. Similarly, Hur et al [13] found a sensitivity and specificity of 89% and 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation